3 Dr. (12th November 2018) - Dovey, Gemma; Banfield-Brown, Danielle; Oliphant, Zoe
Abstract : As trainee doctors who have been fortunate enough to attend training days on clinical leadership and management, we realised how important education on these subjects is. We have personally felt inspired and enthused to use our actual and potential skills as leaders in our everyday clinical practice. We are aware that other doctors may not be lucky enough to receive these opportunities, and we therefore organised an event which provided some factual learning for trainees, but more importantly motivated them to become involved in local leadership opportunities. We ran a one-day symposium for all trainee doctors in our region. We aimed to encourage them to understand the leadership opportunities available, to enable them to reflect on their own qualities as a leader, and to utilise these attributes effectively. Many specialties name 'experience of leadership and management' as an assessment criteria for CCT/ARCPs. Given the pressures on clinical rotas, we designed a day that would satisfy training requirements and also leave trainees enthused and inspired. The majority of feedback that we received about our symposium was qualitative. We were pleased to note that the majority of trainees had viewed it as a good place to start their leadership journey, wanted to discover more about leadership opportunities in their local area, and wanted to improve their professional skills. We anticipate that the trainees who attended the symposium will now go back to their individual trusts and use their renewed enthusiasm in their day to day practice and quality improvement work. We also hope that their view of the role of managers may be more positive, leading to better working relationships.